Alveolar permeability in HIV antibody positive patients with Pneumocystis carinii pneumonia. Issue 4 (August 1987) - O'Doherty, M J; Page, C J; Bradbeer, C S; Shahmanesh, M; Edwards, A; Barlow, D; Bateman, N T; Croft, D N
Abstract : Pulmonary permeability was assessed using the technique of 99mTc (technetium-99m) diethylene triamene pentacetic acid (DTPA) aerosol transfer in 10 patients who had antibodies to human immunodeficiency virus (HIV) and were non-smokers and in 20 HIV antibody positive smokers. Five patients had Pneumocystis carinii pneumonia (PCP) proved by transbronchial lung biopsy; four were non-smokers and one a smoker. Two findings emerged: patients with PCP had greater epithelial permeability than non-smokers and smokers; and the permeability curves were monophasic in smokers and non-smokers, but biphasic in patients with PCP. The biphasic curve observed is indicative of diffuse alveolar damage and might be useful to predict PCP in patients with antibodies to HIV who have normal chest radiographs. As the study was of only five patients with PCP, however, further studies are necessary to confirm this observation.